Development of the Automated System for Radiation Risk Analysis: goals, tasks and the vision for progress - L. V. Repin; R. R. Akhmatdinov; A. M. Biblin; V. S. Repin (Радиационная гигиена)
This paper describes the preconditions of creation and the process of development of the Automated System for Radiation Risk Analysis. Three main objectives for the development of an automated system for radiation risk analysis were identified: creation of a tool for the development and scientific justification of hygienic standards and other protective quantities in the field of ionizing radiation application; practical implementation of the principles of justification and optimization in radiation protection on the basis of monetary assessment of radiation health risks; and comparative analysis of risks of different nature on the basis of comparable indicators of population health. The Russian software platform 1C: Enterprise was chosen as the development platform for the Automatized System for Radiation Risk Analysis. The choice of this platform was related to simplification of integration with other computer systems being developed at the Research Institute of Radiation Hygiene after Prof. P.V. Ramzaev, such as the Automated System for Radiation Exposure Control of Rospotrebnadzor. Before the practical development of the system in accordance with the terms of reference, the main parameters in view of its interaction with the user were determined: arrangement of the user interface elements, main input parameters, primary calculated indicators and output calculation results, etc. The estimation of annual increase in the probability of radiation-induced malignant neoplasms depending on the organ dose, sex and age of the exposed person and other parameters according to the models of the UN Scientific Committee on the Effects of Atomic Radiation, the U.S. Environmental Protection Agency and Publications 103 and 152 of the International Commission on Radiological Protection was implemented in the system. The capabilities of the system include calculation of a number of modern lifetime radiation risk indicators used for risk characterization in various scientific publications over the last 35 years, including calculation of population risks based on national medical and demographic data of several dozen states published over the last 50 years.